The impact of incentivizing participation in voluntary green programs on service satisfaction - Deema Abdallah Bazaraa; Abeer Mahrous; Mohamed Elsharnouby (Cairo : Deema Abdallah Bazaraa, 2020)
Purpose: The purpose of this research is to examine the effect of participation in green programs on warm glow and satisfaction and how incentivizing participation can play a moderating role. Design/methodology/approach: Two pilot studies and three experimental studies were carried out. One pilot study aimed at determining what amount of incentive is considered to be low or high while the other aimed at testing the experiments on a small scale before carrying them out on a large scale. Regarding the experiments, the first study aimed at examining the effect of green program participation on warm glow and how warm glow mediates the relationship between participation in voluntary green programs and satisfaction.The second and third studies aimed at examining how manipulating the type and level of incentives can affect the relationship between participation in voluntary green programs, warm glow and satisfaction. Data were tested and analyzed using SPSS and PROCESS macro. Findings: This research finds that compared to green programs using no incentive, green programs using low self-benefiting incentive decrease satisfaction among the green program{u2019}s participants group while increase satisfaction among the green program{u2019}s non-participants group. Green programs using high self-benefiting incentive increase satisfaction among the green program{u2019}s participants group as well as the green program{u2019}s non-participants group.Green programs using low other-benefiting incentive increase satisfaction among the green program{u2019}s participants group while decrease satisfaction among the green program{u2019}s non-participants group. Green programs iv using high other-benefiting incentive increase satisfaction among the green program{u2019}s participants group while decrease satisfaction among the green program{u2019}s non-participants group. Using low or high other-benefiting incentives in green programs produces similar results in terms of satisfaction level among both groups
Thesis (M.Sc.) - Cairo University - Faculty of Commerce - Department of Business Administration
Issued also as CD
Keywords: Green marketing; Green programs; Warm glow